2005
DOI: 10.3200/aeoh.60.2.96-105
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health and Indoor Air Pollution at High Elevation

Abstract: In this research, the authors sought to provide experimental data on indoor air quality, and the resulting respiratory impact, for a high-elevation (4550 m), rural community in Ladakh, India. This community is of interest because the primarily nomadic residents burn biomass inside the home for heating and cooking. The concentrations of particulate matter (PM), endotoxin, and carbon monoxide were determined for 6 homes. Lung function data and induced sputum samples were collected for 9 female test-home subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
(20 reference statements)
1
12
0
3
Order By: Relevance
“…Rosati et al (12) in their study reports mean levels of total PM ranging from 2 to 7 mg/ m 3 , Hakim (27) estimates the average value at 0.052 mg/m 3 . The limit value set by health authorities in Slovakia is 0.05 mg/m 3 of particles of 10 micrometers in size for a 24 hour exposure (22).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Rosati et al (12) in their study reports mean levels of total PM ranging from 2 to 7 mg/ m 3 , Hakim (27) estimates the average value at 0.052 mg/m 3 . The limit value set by health authorities in Slovakia is 0.05 mg/m 3 of particles of 10 micrometers in size for a 24 hour exposure (22).…”
Section: Discussionmentioning
confidence: 95%
“…PM, CO, and CO 2 have been linked to biomass usage in a number of recent studies (1012, 14, 1621, 23, 25–27). In some studies, additional pollutants were sampled,such as endotoxin (12), nitric oxides (13, 14), sulfur dioxide (14, 27), and the 2.5 micrometer fraction of the PM (18, 20). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median endotoxin values were 43 EU/m 3 in wood-burning homes and 365 EU/m 3 in dung-burning homes in Nepal 10 . Another study on airborne endotoxin from biomass fuel in the Ladakh region of India reported endotoxin level of 190 EU/m 3 in a rural community settings 28 . Our results in the range of 315-430 EU/m 3 in biomass burning homes and are in line with the findings of these studies suggesting burning of biomass fuels to be associated with airborne endotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…1824 However, there are very few Indian studies that link air pollution exposure to lung function deterioration, underlining the need for systematic studies. 21 …”
mentioning
confidence: 99%